KONSEP AWET MUDA DALAM AL-QUR'AN: ASPEK SPIRITUAL DAN KESEHATAN - Zara; Safitri Hasibuan; Ali Akbar (Ar-Rasyid: Jurnal Publikasi Penelitian Ilmiah, 2025)
This study explores the concept of youthful vitality in the Qur’an by examining its spiritual and health aspects. The research aims to understand how spiritual values and health principles in the Qur’an contribute to human physical vitality and endurance. The method used is a literature review and thematic analysis of Qur’anic verses related to physical and spiritual health. The findings reveal that the Qur’an views youthful vitality not merely as a physical phenomenon but as a result of harmony between a pure heart, strong faith, and divinely recommended healthy lifestyle. Therefore, the concept of youthful vitality in the Qur’an holds a holistic meaning that encompasses the balance between soul and body.